2019
DOI: 10.1002/smll.201904670
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Colloidal Transition Metal Dichalcogenide Library to ReS2 Nanosheets for Application in Gas Sensing and Electrocatalysis

Abstract: Among the large family of transition metal dichalcogenides, recently ReS2 has stood out due to its nearly layer‐independent optoelectronic and physicochemical properties related to its 1T distorted octahedral structure. This structure leads to strong in‐plane anisotropy, and the presence of active sites at its surface makes ReS2 interesting for gas sensing and catalysts applications. However, current fabrication methods use chemical or physical vapor deposition (CVD or PVD) processes that are costly, time‐cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 119 publications
(315 reference statements)
0
40
1
Order By: Relevance
“…[203] Hence, the design and fabrication of ReX 2 -based materials for sensor applications have intrigued considerable attention, and several novel ReX 2 -based sensors have been developed recently. [28,[204][205] Fu's group presented a smart self-adapting wettability (SAW) of ReS 2 under sustaining light irradiation, where the ReS 2 film was grown on the Si/SiO 2 substrate via CVD growth. [204] Figure 15a shows the schematic diagram of the SAW process, and the corresponding contact angle variation reflects the wetting behavior during the whole process (Figure 15b).…”
Section: Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…[203] Hence, the design and fabrication of ReX 2 -based materials for sensor applications have intrigued considerable attention, and several novel ReX 2 -based sensors have been developed recently. [28,[204][205] Fu's group presented a smart self-adapting wettability (SAW) of ReS 2 under sustaining light irradiation, where the ReS 2 film was grown on the Si/SiO 2 substrate via CVD growth. [204] Figure 15a shows the schematic diagram of the SAW process, and the corresponding contact angle variation reflects the wetting behavior during the whole process (Figure 15b).…”
Section: Sensormentioning
confidence: 99%
“…[ 203 ] Hence, the design and fabrication of ReX 2 ‐based materials for sensor applications have intrigued considerable attention, and several novel ReX 2 ‐based sensors have been developed recently. [ 28,204–205 ]…”
Section: Application Of Rex2mentioning
confidence: 99%
“…The electrodes were fabricated by depositing the TaS 2 nanoflake dispersions (catalyst mass loading = 0.2 mg cm −2 ) onto carbon nanotube (CNT)-based papers (i.e., buckypapers) through vacuum filtration method (see details in Supporting Information, Methods). The choice of buckypaper as the support relies on data from our previous works, in which we showed that the porosity of the CNT tangle promotes the adhesion of the TMDC films without the need of any ion conducting binders, [65,66] such as sulfonated tetrafluoroethylene-based fluoropolymer copolymers (e.g., Nafion). The surface morphology of the as-prepared electrodes was characterized by SEM imaging ( Figure S12, Supporting Information).…”
Section: Fabrication and Characterization Of Tas 2 -Based Electrodesmentioning
confidence: 99%
“…191,192 Hence, modifying the metalsemiconductor contact interface is an effective strategy to improve device performance. Specifically, using metallic 2D materials (graphene, 193 some 1 T phase TMDs 47,187,[194][195][196][197] ) as electrodes for (opto)electronics through epitaxy growth 35 or phase transition 198,199 will alleviate the pining effect. In addition, transferring the prefabricated metal electrodes can also avoid creating defects and strains, resulting in an atomically sharp and near perfect metal/2D semiconductor interface.…”
Section: Discussionmentioning
confidence: 99%